Tính:
a) \( - 2{x^2} + 6{x^2}\); b) \(4{x^3} - 8{x^3}\);
c) \(3{x^4}( - 6{x^2})\); d) \(( - 24{x^6}):( - 4{x^3})\).
Tính:
a) \(({x^2} - 6)({x^2} + 6)\);
b) \((x - 1)({x^2} + x + 1)\).
a) \(\begin{array}{l}({x^2} - 6)({x^2} + 6) = {x^2}({x^2} + 6) + ( - 6).({x^2} + 6) = {x^2}.{x^2} + {x^2}.6) + ( - 6).{x^2} + ( - 6).6\\ = {x^4} + 6{x^2} - 6{x^2} - 36 = {x^4} - 36\end{array}\)
b) \(\begin{array}{l}(x - 1)({x^2} + x + 1) = x({x^2} + x + 1) + ( - 1)({x^2} + x + 1) = x.{x^2} + x.x + x.1 + ( - 1).{x^2} + ( - 1).x + ( - 1).1\\ = {x^3} + {x^2} + x - {x^2} - x - 1 = {x^3} - 1\end{array}\)
Cho x^2-x=8. Tính:
A=x^6-2x^4-x+x^2+x^3
Tính:
a) \(({x^3} + 1):({x^2} - x + 1)\);
b) \((8{x^3} - 6{x^2} + 5):({x^2} - x + 1)\).
a)
Vậy \(({x^3} + 1):({x^2} - x + 1) = x + 1\).
b)
Vậy \((8{x^3} - 6{x^2} + 5) = ({x^2} - x + 1)(8x + 2) + ( - 6x + 3)\)
Tính:
a) \(\dfrac{x+1}{2x-6}+\dfrac{2x+3}{x^2+3x}\)
b) \(\dfrac{3}{2x+6}-\dfrac{x-6}{3x^2+6}\)
c) \(\dfrac{2x+6}{3x^2-x}:\dfrac{x^2+3x}{1-3x}\)
c: \(=\dfrac{2\left(x+3\right)}{x\left(3x-1\right)}\cdot\dfrac{-\left(3x-1\right)}{x\left(x+3\right)}=\dfrac{-2}{x^2}\)
Tính:
a) 9/5 + 2/5 x 4/6
b) 3/8 x 2 - 6/7 x 1/3
a,`9/5+2/5xx4/6=9/5+4/15=27/15+4/15=31/15`
b,`3/8xx2-6/7xx1/3=3/4-2/7=21/18-8/28=13/28`
a) 9/5+ 4/15
= 27/15+4/15
= 31/15
b) 3/4- 2/7
= 13/28
\(a,=\dfrac{9}{5}+\dfrac{4}{15}=\dfrac{27}{15}+\dfrac{4}{15}=\dfrac{31}{15}\\ b,=\dfrac{3}{4}-\dfrac{2}{7}=\dfrac{13}{28}\)
Bài 1: Tính:
a) x^2-9/2x+6 : 3-x/2
b) 2x/x-y - 2y/x-y
c) x+15/x^2-9 + 2/x+3
d)x+y/2x+2y - x-y/2x+2y - y^2+x^2/y^2-x^2
Bài 2: Rút gọn:
a) x^3-x/3x+3
b) x^2+3xy/x^2-9y^2
Bài 3: Thực hiện phép tính:
a) x/x-3 + 9-6x/x^2-3x
b) 6x-3/x : 4x^2-1/3x^2
Tính:
a) \(({x^2} + 2x + 3) + (3{x^2} - 5x + 1)\);
b) \((4{x^3} - 2{x^2} - 6) - ({x^3} - 7{x^2} + x - 5)\);
c) \( - 3{x^2}(6{x^2} - 8x + 1)\);
d) \((4{x^2} + 2x + 1)(2x - 1)\);
e) \(({x^6} - 2{x^4} + {x^2}):( - 2{x^2})\);
g) \(({x^5} - {x^4} - 2{x^3}):({x^2} + x)\).
a) \(({x^2} + 2x + 3) + (3{x^2} - 5x + 1) = ({x^2} + 3{x^2}) + (2x - 5x) + (3 + 1) = 4{x^2} - 3x + 4\);
b) \(\begin{array}{l}(4{x^3} - 2{x^2} - 6) - ({x^3} - 7{x^2} + x - 5) = 4{x^3} - 2{x^2} - 6 - {x^3} + 7{x^2} - x + 5\\ = (4{x^3} - {x^3}) + ( - 2{x^2} + 7{x^2}) - x + ( - 6 + 5) = 3{x^3} + 5{x^2} - x - 1\end{array}\);
c) \(\begin{array}{l} - 3{x^2}(6{x^2} - 8x + 1) = - 3{x^2}.6{x^2} - - 3{x^2}.8x + - 3{x^2}.1\\ = - 18{x^{2 + 2}} + 24{x^{2 + 1}} - 3{x^2} = - 18{x^4} + 24{x^3} - 3{x^2}\end{array}\);
d) \(\begin{array}{l}(4{x^2} + 2x + 1)(2x - 1) = (4{x^2} + 2x + 1).2x - (4{x^2} + 2x + 1).1 = 4{x^2}.2x + 2x.2x + 1.2x - 4{x^2} - 2x - 1\\ = 8{x^{2 + 1}} + 4{x^{1 + 1}} + 2x - 4{x^2} - 2x - 1 = 8{x^3} + 4{x^2} + 2x - 4{x^2} - 2x - 1 = 8{x^3} - 1\end{array}\);
e) \(\begin{array}{l}({x^6} - 2{x^4} + {x^2}):( - 2{x^2}) = {x^6}:( - 2{x^2}) - 2{x^4}:( - 2{x^2}) + {x^2}:( - 2{x^2})\\ = - \dfrac{1}{2}{x^{6 - 2}} + {x^{4 - 2}} - \dfrac{1}{2}{x^{2 - 2}} = - \dfrac{1}{2}{x^4} + {x^2} - \dfrac{1}{2}.\end{array}\);
g)
\(({x^5} - {x^4} - 2{x^3}):({x^2} + x)=x^3-2x^2\)
Tính:
a) \((8{x^3} + 2{x^2} - 6x):(4x)\);
b) \((5{x^3} - 4x):( - 2x)\);
c) \(( - 15{x^6} - 24{x^3}):( - 3{x^2})\).
a) \(\begin{array}{l}(8{x^3} + 2{x^2} - 6x):(4x) = 8{x^3}:(4x) + 2{x^2}:(4x) - (6x):(4x)\\ = (8:4).({x^3}:x) + (2:4).({x^2}:x) - (6:4).(x:x)\\ = 2{x^2} + \dfrac{1}{2}x - \dfrac{3}{2}\end{array}\)
b) \(\begin{array}{l}(5{x^3} - 4x):( - 2x) = 5{x^3}:( - 2x) - 4x:( - 2x) = (5: - 2).({x^3}:x) - (4: - 2).(x:x)\\ = - \dfrac{5}{2}{x^{3 - 1}} - ( - 2) = - \dfrac{5}{2}{x^2} + 2\end{array}\)
c) \(\begin{array}{l}( - 15{x^6} - 24{x^3}):( - 3{x^2}) = ( - 15{x^6}):( - 3{x^2}) + ( - 24{x^3}):( - 3{x^2})\\ = ( - 15: - 3).({x^6}:{x^2}) + ( - 24: - 3).({x^3}:{x^2})\\ = 5.{x^{6 - 2}} + 8.{x^{3 - 2}} = 5{x^4} + 8x\end{array}\)
Tính:
a) 2/3 + 1/6 - 7/12 = ...
b) (2/3 + 3/4) x 6 = ...